Pemberdayaan Guru dan Orang Tua tentang Penanganan Kegawatdaruratan Rongga Mulut Anak Pra Sekolah - Ricky Anggara Putranto; Tiarma Talenta Theresia; Johan Arief Budiman; Tien Suwartini; Alfred Pakpahan (LPPM Akbid Harapan Ibu Pekalongan, 2023)
Oral emergencies are trauma involving the teeth and the supporting structures of the teeth. This trauma can be in the form of open wounds, broken teeth and loose teeth. During the COVID-19 pandemic, mothers had more time to spend with their children, so they were expected to be able to provide quick and appropriate action if their children experienced trauma to their teeth. This empowerment activity aims to increase knowledge and skills in handling oral emergencies. This Community Service activity was carried out by the Trisakti University Faculty of Dentistry Team for Teachers and Parents of Kindergarten Al Hidayah 2 Kelapa Gading on December 1, 2022. Counseling and training were carried out offline using presentations on open wounds, broken teeth loose teeth, and first aid that can be done at home. Training and counseling was carried out to 46 participants for 60 minutes. Participants' knowledge was assessed by pre-test and post-test using Google Form. From the results obtained, it was seen that there was an increase in the knowledge of the counseling participants by 13.5% (mean pre-test score was 28.9 ± 14.6 and mean post-test score was 68 ± 15.3).